Food colloid-based delivery systems for tackling age-related macular degeneration by enhancing carotenoid bioavailability: A review - Erin Kuo; David Julian McClements (Food Hydrocolloids for Health, 2022)
Over the past century, there has been a large increase in the life expectancy of people around the globe, which means there has been a rise in diseases of the elderly. Age-related macular degeneration (AMD) is a sight-threatening condition of the eye characterized by a loss of central vision. Research suggests that macular pigment carotenoids, such as lutein and zeaxanthin, may inhibit the onset of this disease by protecting the eye from damaging light and oxidation. These carotenoids are chemically reactive hydrophobic molecules with a low water-solubility, chemical stability, and bioavailability. Consequently, many carotenoid-rich foods and supplements are not absorbed by the human body and do not exhibit their beneficial effects on eye health. In this article, we review the prevalence and characteristics of AMD, the sources of macular pigment carotenoids in foods, the factors limiting their bioavailability, and analytical approaches available to study their bioavailability and bioactivity. We then discuss different strategies for increasing the concentration of bioavailable macular pigment carotenoids in the human diet, including dietary sources, supplements, functional foods, and excipient foods, with an emphasis on colloidal systems that can be used for this purpose.